Contributions of bats to the local economy through durian pollination in Sulawesi, Indonesia - Sheherazade; Ober, H.K.; Tsang, S.M. (Wiley, 2019)
Durian is economically important for local livelihoods in Indonesia. Our study investigated the identity of pollinators of semi‐wild durian and subsequently estimated the economic contribution of these pollination services. We conducted pollination exclusion experiments and deployed camera traps at durian trees from October 2017 to January 2018 in an area where the local economy depends on durian production in West Sulawesi, Indonesia. Durian flowers in the experiment that were accessible to bats had significantly higher fruit set compared with flowers that were completely closed to animal visitors or those that could only be visited by insects, suggesting that bats were the primary durian pollinator. The small, highly nectarivorous cave nectar bat (Eonycteris spelaea) visited more inflorescences (n = 25) and had visits of much longer duration ( = 116.87 sec/visit) than the two species of flying foxes: Pteropus alecto (n = 7 inflorescences visited, = 11.07 sec/visit) and Acerodon celebensis (n = 6 inflorescences visited, = 11.60 sec/visit). Visits by large and small bats were influential in differentiating successful durian fruit production from unsuccessful. Using a bioeconomic approach, we conservatively estimate that bat pollination services are valued at ~$ 117/ha/fruiting season. By demonstrating an ecological link between bats and the local economy, this research provides an urgent message for Southeast Asian governments regarding the need to promote bat conservation in order to increase the production of durian grown under semi‐wild conditions.Abstract in Indonesia is available with online material.